Anatomy of Piper colubrinum Link. - REMASHREE, P N RAVINDRAN, A B (Journal of Spices and Aromatic Crops, 1998)
Piper colubrimum exhibits dimorphic branching (orthotropic and plagiotropic shoots) as in many other Piper species. The stem exhibits anomalous secondary growth. The number and size of peripheral and medullary bundles show variations in the two types of shoots. Secondary growth occurs only in the peripheral bundles. In a mature stem (7 mm thickness), the average length and width of xylem vessel is 258 flm and 73.8 flm respectively, in peripheral bundles, whereas in medullary bundles it is 195 flm and 81.5 flm, respectively. Vessels are pitted with simple perforation plates. Tracheids have scalariform and annular thickening. Libriform unseptate fibres are also present. Comparative stem anatomy of P. nigrum and P. colubrimum shows similarities. However, the aerial and underground roots show variations especially in the number of vascular elements. Secondary thickening in root is comparable to that in dicots. The aerial roots undergo transformation in internal structure when they enter soil and grow as underground roots.